Spontaneous renal adenocarcinoma in a Syrian hamster (Mesocricetus auratus): frequency, morphological and immunohistochemical findings - Trotte, Marcele N. de Sousa; Pinto, Luciana W.; Santos, Belmira F. dos; Menezes, Rodrigo C.; Tortelly, Rogerio (Brazilian Journal of Veterinary Pathology, 2010)
A spontaneous adenocarcinoma occurred in one (0.22%) adult male Syrian hamster out of 443 necropsied from a breeding animal house of the state of Rio de Janeiro, Brazil. Gross inspection showed that the renal neoplasm consisted of a unilateral single white nodule of hard consistency located in the cortex, measuring 5 mm in diameter. Microscopically, the renal epithelial cells were markedly pleomorphic and presented an abundant granular eosinophilic cytoplasm. Cells were cuboidal and mainly formed trabeculae of various widths without a lumen and also formed solid areas. There were necrotic areas and three mitotic figures per 30 high-power fields. No intravascular invasion or metastasis was observed. Positive expression of vimentin and negative expression of cytokeratin 7, pan-cytokeratin and CD10 were observed in the tumor. The histopathology and immunohistochemical profile of the renal tumor suggested the diagnosis of the eosinophilic variant of adenocarcinoma, which was reported for the first time in this species.